Culpa in Contrahendo: A Testimony to the Changing Methodologies in Private International Law - Maria-Anna Zachariasiewicz; Maciej Zachariasiewicz (Review of European and Comparative Law, 2025)
The concept of culpa in contrahendo traditionally encompasses cases of disloyal conduct by the parties during the negotiation stage of a contract. It applies to a broad range of factual scenarios. Furthermore, the legal nature of culpa in contrahendo has long been the subject of debate, with some legal systems favouring its classification as a contractual matter and others as a delict. In the realm of private international law, these issues present significant challenges in terms of legal characterization as aptly demonstrated by the well-known case of Tacconi v. Wagner (2002), in which the Court of Justice of the European Union (CJEU) delineated the application of Articles 5(1) and 5(3) of the Brussels Convention (now Articles 7(1) and 7(2) of the Brussels I bis Regulation). The CJEU favored a tort-based qualification for claims arising from the breach of pre-contractual duties, but only insofar as they were not grounded in “obligations freely assumed by one party towards another.” Despite the stance taken by the CJEU – which reflects the traditional conflict-of-laws approach, strictly distinguishing torts from contracts – the EU legislator, in Article 12 of the Rome II Regulation (2007), adopted a solution that can be described as an “accessory connection.” According to this provision, the law applicable to a non-contractual obligation arising from dealings prior to the conclusion of a contract – regardless of whether the contract was ultimately concluded – is the law that applies to the contract or that would have applied to it had it been entered into. Only in exceptional cases will the applicable law be determined by connecting factors traditionally associated with torts, such as the place of damage (Article 12(2)). Thus, regardless of the delictual nature of culpa in contrahendo, such obligations are governed by the law applicable to the contract, even in instances where the contract never materialized. The article explores various approaches to the conflict-of-law characterization of pre-contractual liability and contrasts tchem with the pragmatic method of identifying the spatial “center of gravity” of the relevant legal relationship. Additionally, the article examines how the “accessory connection” operates under Article 12 of the Rome II Regulation with respect to pre-contractual liability, highlighting its advantages. It argues that while the adopted solution does not entirely dispense with traditional conflict-of-laws characterization, it significantly diminishes its practical application, as the lex contractus will invariably apply. Consequently, the EU legislator favors an independent localization of the legal relationship based on pragmatic criteria – specifically, an accessory reference to the law applicable to the contract.